PENGARUH KOMPRES ALOE VERA TERHADAP NYERI PAYUDARA PADA MASA NIFAS DI KLINIK BPM MARDIAH & BPM KLAHIJAH KOTA LANGSA - EMILDA . (Poltekkes Kemenkes Surabaya, 2017)
The objective of this research was to identify The Effect of Aloe Vera Compress on Breast Pain during Postpartum Period experienced by mothers at BPM Mardiah Clinic and BPM Khalizah Clinic, Kota Langsa, 2016.The research design used is Quasi Experimental Design with The Posttest Only Control Group Design. This experimental design requires treatments, outcome measures, and experimental units, but it does not use random placements. The Posttest Only Control Group Design needs two types of groups: